Peran Kelompok Sadar Wisata dalam Pengembangan Wisata Coban Goa Jalmo di Kabupaten Pasuruan - Wiluyo, Denny Putro; Ilmi Usrotin Choiriyah (Universitas Muhammadiyah Sorong, 2024)
Tourism Awareness Groups (Pokdarwis) are a resource obtained through local residents who participate and play an important role in efforts to manage and develop tourism potential in an area. The aim of this research is to analyze and describe the role of tourism awareness groups in the development of Coban Goa Jalmo tourism in Cendono Village, Purwosari District, Pasuruan Regency. The approach used in this research is a qualitative approach with descriptive methods. This research uses a purposive sampling technique to consider and determine certain informants who have the ability and understand the problem being studied. The results of this research show that in terms of the facilitating role of the Coban Goa Jalmo Pokdarwis, it raises the social enthusiasm of the community, provides support for tourist facilities even though there are several facilities that need improvement and carries out community organizing. In terms of educational role, Pokdarwis Coban Goa Jalmo provides outreach and training to the community even though community participation and enthusiasm is still minimal. Apart from that, Pokdarwis's representational role in establishing cooperative interactions with various parties and in managing social media is still limited. Then in a technical role, Pokdarwis manages finances based on established technical stages and uses laptops and computers for daily administration activities.